(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Survey the changes in vital signs when pressing the Taichong acupoint in students of Can Tho University of Medicine and Pharmacy in 2024-2025. Research subjects and methods: Conducted on 75 students studying at Can Tho University of Medicine and Pharmacy. The research was conducted using the method of a clinical trial without a control group, comparing the results before and after the test. Results: After pressing the Taichong acupoint for 3 minutes, systolic blood pressure decreased from 114.2 ± 10.81 mmHg to 107.05 ± 10.30 mmHg (p < 0.001), and diastolic blood pressure decreased from 63.73 ± 6.98 mmHg to 60.67 ± 8.32 mmHg (p = 0.002). Pulse rate decreased from 76.91 ± 10.77 beats/minute to 72.81 ± 8.00 beats/minute (p < 0.001), and respiratory rate decreased from 18.4 ± 1.73 beats/minute to 17.64 ± 2.42 beats/minute (p = 0.014). Body temperature changes were not statistically significant, increased from 37.08 ± 0.32°C to 37.09 ± 0.37°C (p = 0.691). The group with high normal blood pressure levels had a greater reduction in systolic blood pressure than the normal blood pressure group (p = 0.033). The group with lean and average body mass index had a greater reduction in pulse rate than the overweight and obese groups (p = 0.044). Conclusions: Acupressure applied to the Taichong point demonstrated a significant effect on blood pressure, pulse rate, and respiratory rate in healthy subjects. In addition, body mass index and initial blood pressure levels were associated with changes in some vital signs after Taichong acupressure intervention.